IDENTIFIKASI BESARAN FISIS FLUIDA PADA ALIRAN IRIGASI JENGGAWAH JEMBER SEBAGAI PENGUATAN PEMAHAMAN KONSEP FISIKA SISWA - Dwi Lestari; Albertus Djoko Lesmono; Maryani Maryani (FKIP Universitas Jember, 2019)
Physics learning at this time, show that the students only memorize the formulas without understanded the actual physical meaning, besides that the learning so far seems monotonous and does not attract students' interest and desire to learn. Science learning that is expected now is creative and innovative science learning is science learning that provides experiences related to students' daily lives. The concept of dynamic fluid is a concept that exists in the real world of students, but the object in dynamic fluid material is difficult to present directly in the class, an example of the application of dynamic fluid in everyday life namely the river. Irrigation in the Jenggawah area of Jember Regency is a place to be identified. This research aimed to identify the physical quantities of fluid in the gutter irrigation river in the Jenggawah area of Jember as strengthening the understanding of students' physics concepts. This research included descriptive research. There were two different measurement points, besides the observation of the type of water flow in the irrigation, as well as the average discharge in the river flow of Jenggawah irrigation gutter for one year from the UPT of Jenggawah Regional Water Resources. The results of identification of fluid physical quantities include irrigation width, sterophome path length, sterophome travel time through trajectory, cross-sectional area, flow velocity, discharge, and flow type. Based on research conducted at the UPT of Jenggawah Regional Water Resources in Jember, the water flowed to the irrigation has a different average discharge rate. Key word: Dynamic fluid, Irrigation, Physics